ANALISIS KEUNTUNGAN PRODUK MIE LOBA RUMAH MAKAN â€œHOPNIâ€ DI DESA KANONANG TIGA KECAMATAN KAWANGKOAN KABUPATEN MINAHASA (The Profit Analysis of Mie Loba Product of Hopni Restaurant in Kanonang Tiga Village Kawangkoan Sub District Minahasa Regency) - Charisma Juliando Kimbal; Joachim N. K. Dumais; Nordy F. L. Waney (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to analyze the benefits of Loba Noodle Products from the "Hopni" Restaurant in Kanonang Tiga Village, Kawangkoan District, Minahasa Regency. This research was conducted in December 2021. The data were analyzed using mathematical calculations using the formula Ï€ = TRâ€“ TC.The research result showed that the "Hopni" loba noodle restaurant business in Kanonang Tiga Village, Kawangkoan Sub District, Minahasa Regency is profitable because the total revenue is Rp. 480.000 per week, the total cost is Rp. 325.953 per week , so the profit obtained is Rp. 154.057 per week.